Risk Factor of Posthemorrhagic Hydrocephalus: Cerebrospinal Fluid Total Protein - Wang, Zhiwen; Chen, Yuxin; Zhou, Xinhui; Wang, Changfeng; Chen, Xianjun; Min, Feixiang; Liu, Ruen; Xiang, Hui (Frontiers in Surgery, 2022)
Objective: Cerebrospinal fluid total protein (CSF-TP) levels in adults with posthemorrhagic hydrocephalus (PHH) are poorly studied. The objective of this study was to explore the characteristics of the CSF-TP levels in patients with PHH. Methods: The clinical data of 156 patients with hemorrhagic brain disease were retrospectively studied and divided into PHH and NPHH groups. Single-factor and multi-factor analyses were performed, and the key role of CSF-TP was evaluated using linear analysis. Results: Among the 156 patients, 85 (54.5%) had PHH, and 34 (21.8%)underwent surgeries. Hypertension (p=0.017), days (total fever time when body temperature 38.5 °C (p=0.040)), Glasgow Coma Scale (GCS) score(p<0.001), and time (from the onset of the disease to the obtainment of CSF-TP after lumbar puncture (p<0.001)) were important factors for PHH. Logistic regression analysis revealed that GCS score <8 (OR=2.943 (1.421-6.097) p=0.004), and CSF-TP×Time 9600 (OR=2.317 1.108-4.849) p =0.026) were independent risk factors for PHH. All CSF-TP values were averaged every 2days. CSF-TP was negatively correlated with time. Linear analysis showed that the CSF-TP in the PHH group was higher than that in the NPHH group at the same onset time, and the duration of it being detected in the CSF was longer. Conclusion: CSF-TP×Time 9600 and GCS score <8 were independent risk factors for PHH. CSF-TP was higher in the PHH group than in the NPHH group.